using complete randomized block design with three replications. The means from each plot were compared by using t-student’s test. Application of inorganic fertilizer resulted in a higher shoot production (at 6 week after planting) and a better quality leaves compared to other treatment. This research revealed that high quality waterleaf can be indicated by some criterias, i.e., higher content of primary metabolites (sugar and protein), secondary metabolites (phenolic, flavonoid, and chlorophyll) - Mualim, Leo; Aziz, Sandra Arifin; Susanto, Slamet; Melati, Maya (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2012)
using complete randomized block design with three replications. The means from each plot were compared by using t-student’s test. Application of inorganic fertilizer resulted in a higher shoot production (at 6 week after planting) and a better quality leaves compared to other treatment. This research revealed that high quality waterleaf can be indicated by some criterias, i.e., higher content of primary metabolites (sugar and protein), secondary metabolites (phenolic, flavonoid, and chlorophyll), and antioxidant capacity (low IC50 value). Therefore, application of inorganic fertilizer in wet season is recommended to produce high yields and high quality water leaf. Keywords: sugar, protein, phenolic, flavonoid, DPPH